Bioaccumulation and toxicity of single‐walled carbon nanotubes to benthic organisms at the base of the marine food chain. (15th April 2013) - Parks, Ashley N.; Portis, Lisa M.; Schierz, P. Ariette; Washburn, Kate M.; Perron, Monique M.; Burgess, Robert M.; Ho, Kay T.; Chandler, G. Thomas; Ferguson, P. Lee
Abstract As the use of single‐walled carbon nanotubes (SWNTs) increases over time, so does the potential for environmental release. This research aimed to determine the toxicity, bioavailability, and bioaccumulation of SWNTs in marine benthic organisms at the base of the food chain. The toxicity of SWNTs was tested in a whole sediment exposure with the amphipod Ampelisca abdita and the mysid Americamysis bahia. In addition, SWNTs were amended to sediment and/or food matrices to determine their bioavailability and bioaccumulation through these routes in A. abdita, A. bahia, and the estuarine amphipod Leptocheirus plumulosus. No significant mortality to any species via sediment or food matrices was observed at concentrations up to 100 ppm. A novel near‐infrared fluorescence spectroscopic method was utilized to measure and characterize the body burdens of pristine SWNTs in nondepurated and depurated organisms. We did not detect SWNTs in depurated organisms but quantified them in nondepurated A. abdita fed SWNT‐amended algae. After a 28‐d exposure to [14C]SWNT‐amended sediment (100 µg/g) and algae (100 µg/g), [14C]SWNT was detected in depurated and nondepurated L. plumulosus amphipods at 0.50 µg/g and 5.38 µg/g, respectively. The results indicate that SWNTs are bioaccessible to marine benthic organisms but do not appear to accumulate or cause toxicity. Environ Toxicol Chem 2013;32:1270–1277. © 2013 SETAC